THE IMPLEMENTATION OF CYBER LITERATURE MICRO/MACRO-FICTION IN NARRATIVE DISCOURSE’S STUDENTS - Hidayatul Nurjanah; Wanda Andres Saputra; Vanessa Agustin (Universitas Duta Bangsa Surakarta, 2026)
Digital and technology have becoming inseparable and integral parts of humans and social life. In many aspects, the exertion of these has extensively spread, including literature. The adjustment of literature establishes cyber literature in the form of digitalized literary works or electronic literature such as e-novel, e-poetry, e-fiction, etc. This research aims at analysing the implementation of cyber literature (micro/macro-fiction) in Narrative Discourse’s students followed by 40 participants. This research employed cyber literature (micro/macro-fiction) theory by Conde & Lopez. This is descriptive qualitative research to describe the phenomenon and its characteristics integrated with digital humanities approach by Capurro. The data were collected using several instruments, i.e. questionnaires, interviews, and documentation. The results indicated that; first, there are four stages of implementation; brainstorming, peer-conference workshops, publication, and comments. These stages were conducted successfully which later continued to the production of cyber literature (micro/macro-fiction). Second, the digital platforms used by the participants are Wattpad (55%), Quora (10%), Twitter (7,5%), Tiktok (7,5%), Youtube (7,5%), Blogspot (5%), Facebook (2,5%). This means that percentage of macro-fiction users are dominant 95% compared to micro-fiction 5%. Third, overall, this implementation process achieved great results since the majority participants voted for 51,25% (agree), 39,1% (strongly agree), 8,3% (neutral), and 1,25% (disagree). Meanwhile, ways to increase reading interest are providing interesting headline/ theme, following trends, creating reading clubs, learning technological development, and building consistency while to gain literary criticism interest are starting to utilize digital literary works, avoiding plagiarism, and respecting the authorship and copyrights.